Cannabinoid Hyperemesis Syndrome - Galli, Jonathan A. (2011)
Coinciding with the increasing rates of cannabis abuse has been the recognition of a new clinical condition known as Cannabinoid Hyperemesis Syndrome. Cannabinoid Hyperemesis Syndrome is characterized by chronic cannabis use, cyclic episodes of nausea and vomiting, and frequent hot bathing. Cannabinoid Hyperemesis Syndrome occurs by an unknown mechanism. Despite the well-established anti-emetic properties of marijuana, there is increasing evidence of its paradoxical effects on the gastrointestinal tract and CNS. Tetrahydrocannabinol, cannabidiol, and cannabigerol are three cannabinoids found in the cannabis plant with opposing effects on the emesis response. The clinical course of Cannabinoid Hyperemesis Syndrome may be divided into three phases: prodromal, hyperemetic, and recovery phase. The hyperemetic phase usually ceases within 48 hours, and treatment involves supportive therapy with fluid resuscitation and anti-emetic medications. Patients often demonstrate the learned behavior of frequent hot bathing, which produces temporary cessation of nausea, vomiting, and abdominal pain. The broad differential diagnosis of nausea and vomiting often leads to delay in the diagnosis of Cannabinoid Hyperemesis Syndrome. Cyclic Vomiting Syndrome shares several similarities with CHS and the two conditions are often confused. Knowledge of the epidemiology, pathophysiology, and natural course of Cannabinoid Hyperemesis Syndrome is limited and requires further investigation.